Optimal federal co-regulation of renewable energy deployment - Jan-Niklas Meier; Paul Lehmann (Helmholtz-Zentrum für Umweltforschung (UFZ), 2020)
In federal countries the allocation of renewable energy (RE) deployment is simultaneously regulated by national and subnational governments. We analyze the efficiency of federal coregulation when different types of policy instruments - price and quantity - are assigned to government levels. Using an analytical model with two regulatory levels, we specify conditions that ensure first-best allocation of RE deployment in equilibrium. These efficiency conditions refer to how the financial burden of the national RE support scheme should be shared among subnational jurisdictions. Under realistic assumptions national price-based regulation is efficient if burden shares are proportional to population shares, regardless of the subnational policy instrument. Contrary, under national quantity-based regulation efficiency conditions depend on the subnational policy instrument. While with subnational price-based regulation burden shares should be oriented towards first-best RE deployment shares, with subnational quantity-based regulation burden shares should be oriented towards population shares.
Keywords: H77; H23; Q48; D47; 330; multi-level governance; environmental regulation; renewable energies; tender scheme; feed-in tariff; spatial planning